Soviet apartheid: Stalin’s ethnic deportations, special settlement restrictions, and the labor army : the case of the ethnic Germans in the USSR - Pohl, Jonathan Otto (Human rights review, 2012)
This article examines the Stalin regime’s treatment of the ethnic Germans in the USSR during the 1940s as a case study in racial discrimination. After 1938, Soviet definitions of nationality became racialized. Systematic repression against certain nationalities in the USSR after this time clearly fit the definition of racial discrimination formulated by scholars in the post-war era. This article examines the separate and unequal institutions of the special settlement regime and labor army imposed upon the ethnic Germans in the USSR during World War II in the context of race as a category constructed along lines of primordial and essentialist views of culture. It also compares the construction of racialized groups and the practice of racial discrimination in the USSR with South Africa during the apartheid era.